Incidence of patient safety events and process-related human failures during intra-hospital transportation of patients: retrospective exploration from the institutional incident reporting system. Issue 11 (3rd November 2017) - Yang, Shu-Hui; Jerng, Jih-Shuin; Chen, Li-Chin; Li, Yu-Tsu; Huang, Hsiao-Fang; Wu, Chao-Ling; Chan, Jing-Yuan; Huang, Szu-Fen; Liang, Huey-Wen; Sun, Jui-Sheng
Abstract : Background: Intra-hospital transportation (IHT) might compromise patient safety because of different care settings and higher demand on the human operation. Reports regarding the incidence of IHT-related patient safety events and human failures remain limited. Objective: To perform a retrospective analysis of IHT-related events, human failures and unsafe acts. Setting: A hospital-wide process for the IHT and database from the incident reporting system in a medical centre in Taiwan. Participants: All eligible IHT-related patient safety events between January 2010 to December 2015 were included. Main outcome measures: Incidence rate of IHT-related patient safety events, human failure modes, and types of unsafe acts. Results: There were 206 patient safety events in 2 009 013 IHT sessions (102.5 per 1 000 000 sessions). Most events (n=148, 71.8%) did not involve patient harm, and process events (n=146, 70.9%) were most common. Events at the location of arrival (n=101, 49.0%) were most frequent; this location accounted for 61.0% and 44.2% of events with patient harm and those without harm, respectively (p<0.001). Of the events with human failures (n=186), the most common related process step was the preparation of the transportation team (n=91, 48.9%). Contributing unsafe acts included perceptual errors (n=14, 7.5%), decision errors (n=56, 30.1%), skill-based errors (n=48, 25.8%), and non-compliance (n=68, 36.6%). Multivariate analysis showed that human failure found in the arrival and hand-off sub-process (OR 4.84, p<0.001) was associated with increased patient harm, whereas the presence of omission (OR 0.12, p<0.001) was associated with less patient harm. Conclusions: This study shows a need to reduce human failures to prevent patient harm during intra-hospital transportation. We suggest that the transportation team pay specific attention to the sub-process at the location of arrival and prevent errors other than omissions. Long-term monitoring of IHT-related events is also warranted.